SEVERE STUNTING: A RARE CASE OF ACROMESOMELIC DYSPLASIA WITH CONCOMITANT GHD - Hui, Saw Shi; Zaini, Azriyanti Binti Anuar; Samingan, Nurshadia Binti; Annie, Leong; Jalaludin, Muhammad Yazid Bin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Acromesomelic dysplasia, type Maroteaux (AMDM) is a rare skeletal dysplasia, characterized by severe disproportionate short stature, primarily affecting the middle and distal segments of the limbs. CASE An 11-year-old female presented with extremely short stature. She was born with a birth weight of 2.6 kg and has been noticed to be short since 2 years old. Her parents were not consanguineous but had a strong family history of short stature. Father’s height was 154 cm (SDS -3.16) and mother’s height was 148 cm (SDS -2.36). The girl has normal intelligence and an unremarkable medical history. She was prepubertal and markedly short with a height of 108.5 cm (SDS -5.03) and a weight of 23.3 kg (SDS - 2.74). Her height was 3 SD below her mid-parental height (MPH SDS-2.3). She had a disproportionate body proportion with an upper segment to lower body segment ratio of 1.25 and shortened middle and distal segments of the limbs. Skeletal survey showed shortening of the radius, ulna, tibia, and fibula as well as short and broad metacarpals and phalanges, with cone-shaped epiphyses. She had an insulin tolerance test that showed peak growth hormone of 8.4 ng/ml and peak cortisol of 586 nmol/L (normal), which suggested isolated severe growth hormone deficiency. Bone age was indeterminate due to abnormal epiphyses. Whole exome sequencing identified compound heterozygous pathogenic variants in NPR2 which is associated with autosomal recessive AMDM. We did not proceed with the 2nd GH test since the genetic results were confirmative. CONCLUSION We described a child with AMDM and severe growth hormone deficiency. Average adult height is estimated to be less than 120 cm. No published data showed that ADMD is related to GHD. Literature reviews showed that 3 AMDM children who received high-dose growth hormone treatment (0.05- 0.1 mg/kg/day) had positive effects on height improvements.